Analisis Tingkat Kepercayaan Diri Peserta Didik Dalam Mengikuti Ekstrakurikuler Futsal di Madrasah Muallimin Yogyakarta - Faizin, Muhammad Noor; Tomolius, Tomolius; Sukamti, Endang Rini (Jurnal Kepelatihan Olahraga, 2024)
The purpose of this study was to determine how much the level of self-confidence of students in participating in extracurricular futsal activities at Madrasah Muallimin Yogyakarta. This research is quantitative descriptive research. The data collection technique used in this research uses instruments in the form of (questionnaires). The population in this study were students who participated in extracurricular futsal activities at Madrasah Muallimin Yogyakarta, totalling 20 people . The sampling technique in this study was total sampling or involved the entire sample. The data analysis technique in this study used descriptive presentation data analysis techniques. The results showed that the level of self-confidence of students in participating in extracurricular futsal activities at Madrasah Muallimin Yogyakarta in the "very low" category was 5.00% (1 student), "low" was 30.00% (6 students), "sufficient" was 30.00% (6 students), "high" was 30.00% (6 students), and "very high" was 5.00% (1 student). Thus it can be concluded that the level of self-confidence of students in participating in futsal extracurricular activities at Madrasah Muallimin Yogyakarta is quite high.